Open and Distance Learning (ODL): preferences, issues and challenges amidst Covid-19 Pandemic / Norazrina Ag-Ahmad - Ag-Ahmad, Norazrina (Universiti Teknologi MARA, Kedah, 2020)
In times of crisis and the global spread of Covid-19 pandemic, the world has observed exponential growth of online education as educators and students are required to stay at home and resume with online learning entirely. With the new norms in education, come new experiences and challenges. The demands in online learning have pushed both students and educators to maximise their ICT skills and some to be unwillingly ready for the new normal. Students have no choice but to keep up with the requirements and challenges of Open and Distance Learning (ODL). Thus, the purpose of this study is to describe the ODL experiences of tertiary students particularly their preferences, their views of the instructional technology as well as the issues that arise in the integration of their courses in the new online class structure. This study used a mixed-method approach whereby questionnaires were distributed to 68 respondents, and further open-ended questions were asked to gather insights regarding their overall views of ODL. The findings showed that aside from connectivity problems, most students found that online learning was difficult for them because they had a lot of distractions at home, which affected their focus, and understanding of the lessons. Thus, it can be concluded that most of the students perceived that Malaysian institutions and students are partially ready for ODL and more time is needed to adapt to the new changes which require empathy, creativity and a great deal of effort.